7 Secrets of Highly Effective Social Impact Communicators How to Grow Your Influence to Solve Society's Most Pressing Challenges - Birt, Nate. (Berkeley, CA : Apress : Imprint: Apress, 2023)
Social impact communication is quickly becoming a mandatory skill for leaders of modern businesses and nonprofits at all levels of an organization. Yet using strategy, language and influence to advance game-changing societal breakthroughs isn't something most people learn in college. This book provides a pathway for empathy, clarity and persuasive communication to advance the social impact work that can help people, their families and society. Too many organizations treat social impact communication and programmatic leadership as "just another marketing project." It's a missed opportunity for businesses seeking to add value to society and deepen their client/customer relationships. What's more, it directly damages other aspects of organizations' ESG priorities- specifically, their cultivation of a healthy, safe and engaged workplace with team members whose personal values and professional activities are in harmony. Journalist and social impact business executive Nate Birt walks you through the essential mindset shifts and principles needed perform the social impact work that matters and have confidence your headed toward true north. The book includes firsthand insights, how-to strategies and social impact leadership anecdotes, along with insights and tips from dozens of social impact communicators. Each chapter concludes with a call for personal reflection or action that features a series of question-based prompts to encourage further introspection and journaling. .
1. Secret #1: Highly Effective Social Impact Communicators ... Care More About the Mission Than the Words -- 2. Secret #2: Highly Effective Social Impact Communicators ... Are Astute Translators Inside and Outside of Their Organizations -- 3. Secret #3: Highly Effective Social Impact Communicators ... Leverage the Strengths of Their Personal Values to Tell Compelling Stories -- 4. Secret #4: Highly Effective Social Impact Communicators ... Embrace the Renewable Fuel of Teamwork -- 5. Secret #5: Highly Effective Social Impact Communicators... Reframe Every Setback as the Crest of a Hill -- 6. Secret #6: Highly Effective Social Impact Communicators ... Cede Perfection to the Messy Reality of Change-making -- 7. Secret #7: Highly Effective Social Impact Communicators...Build Personal and Professional Legacies That Will Outlive Them and Their Careers -- 8. Some Helpful Resources for Social Impact Communicators. .
Keywords: Entrepreneurship; New business enterprises; Industrial management -- Environmental aspects; Nonprofit organizations; Business ethics; Environmental education; Environmental economics; Entrepreneurship; Corporate Environmental Management; Non-Profit Organizations and Public Enterprises; Business Ethics; Environmental and Sustainability Education; Environmental Economics